INTRODUCING NEW ASPECTS OF BEAUTY TO GENERATION Z WOMEN: CASE STUDY OF WARDAH BEAUTY PRODUCTS VISUAL ADVERTISING - AA, 1Khoirus Sa adah; Agristi, Elfrida Diva; Nisa, Mir Atun; Susanto, Putu Chris; Dewi, Putu Chrisma (LPPM Universitas Dhyana Pura, 2022)
ABSTRACTVisual advertising in the form of video commercials is one of the most influential means of promotion,because its reach is very broad. Many product advertisers want to convey a message to their viewers tobe the center of attention, one of which is Wardah beauty products. A product that uses the